Empowerment of the Younger Generation through the Application of Stem Cutting Technology and the Four Pillars of Robusta Coffee Cultivation in Pupuan Village, Tabanan - Yohanes Parlindungan Situmeang; I Gede Pasek Mangku; Ni Luh Putu Indiani; Naori Miyazawa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Robusta coffee productivity in Pupuan Village, Tabanan Regency, has not yet reached its optimal potential. The main obstacle lies in the use of conventional seed-based seedlings, which cause high genetic variability due to the self-incompatible nature of Robusta coffee. To address this, the Community Engagement program focuses on empowering the younger generation by transferring vegetative propagation technology (stem cuttings) and implementing the Four Pillars of Cultivation Technology. This program involved 30 students from SMA Negeri 1 Pupuan as target partners. Quantitative evaluation using pre- and post-test instruments showed significant changes in knowledge, with students' technical understanding scores increasing by 33.87% (p < 0.001) after the intervention. As a tangible result, participants demonstrated a deep understanding of the Standard Operating Procedures (SOPs) for stem-cutting propagation, including orthotropic shoot selection, the application of natural Plant Growth Regulators (PGRs) such as shallot extract, and microclimate regulation. To ensure sustainability, a collective Action Plan is needed that engages the younger generation in selecting and implementing this technology. This step is expected to encourage increased coffee plantation productivity in the future while strengthening the regeneration of young farmers. Contribution to Sustainable Development Goals (SDGs):SDG   2: Zero HungerSDG 12: Responsible Consumption and ProductionSDG 13: Climate ActionSDG 15: Life on Land